ON THE ORIGINS OF AMPHORA ZEEST 90/DYCZEK 25 – ULTIMATE SOLUTION? - Dyczek, Piotr (Rei Cretariae Romanae Fautorum Acta, 2024)
Amphorae of Zeest 90 type were classified by I.B. Zeest in 1960, based on archaeological material from the Bosporan Kingdom. Initially, the impression was that they did not range outside the Black Sea littoral, that is, until it was noted that the form resembles vessels classified first as type 24 by H. Dressel and then ten years later as type XXIX by A. Mau. In spite of this, it was not until 2001 that it was finally understood that Dressel 24 and Zeest 90 actually represented the same type; hence, practically nothing has been written about Dressel 24, while Zeest 90 is present solely in Russian and Romanian publications. My interest in the amphorae grew when dozens of these vessels were found during excavations at the hospital of the First Italic Legion in Novae.